Genetic evidence for the liver-brain axis: lipid metabolism and neurodegenerative disease risk - Zeyu Wang; Zixiao Yin; Guangyong Sun; Dong Zhang; Jianguo Zhang (Lipids in Health and Disease)
Abstract Background The liver‒brain axis is critical in neurodegenerative diseases (NDs), with lipid metabolism influencing neuroinflammation and microglial function. A systematic investigation of the genetic relationship between lipid metabolism abnormalities and ND, namely, Alzheimer's disease (AD), Parkinson's disease (PD), multiple sclerosis (MS), and amyotrophic lateral sclerosis (ALS), is lacking. To assess potential causal links between ND and six lipid parameters, two-sample Mendelian randomization (MR) was used. Methods Large-scale European ancestry GWAS data for lipid parameters and ND (AD, ALS, PD, and MS) were used. Genetic variants demonstrating significant correlations (P < 5 × 10−8) with lipid metabolism parameters were identified and employed as instrumental variables (IVs) after proper validation. The research incorporated UK Biobank genomic data to examine associations between genetic variants and lipid metabolism parameters. The analysis included primary MR, sensitivity analyses, and multivariable MR, which considered potential mediators. Results MR via the inverse-variance weighted method revealed causal effects of cholesterol (CHOL, OR = 1.10, 95% CI: 1.03–1.18, P = 4.23 × 10⁻3) and low-density lipoprotein cholesterol (LDLC, OR = 1.10, 95% CI: 1.03–1.17, P = 3.28 × 10⁻3) on the risk of ALS, which were validated across multiple methods. Potential correlations were observed between ApoB and ALS and inversely correlated with AD, whereas no significant associations were found for PD or MS. CHOL and LDLC associations with ALS demonstrated no significant heterogeneity or pleiotropy, supporting their reliability. Conclusions Higher CHOL and LDLC levels were associated with increased ALS risk, suggesting a potential causal link, and supporting the liver‒brain axis hypothesis in ND. Current genetic evidence does not support a significant role for lipid metabolism in PD and MS etiology, suggesting the relationship between lipid metabolism and other NDs may be more complex and warrants further investigation.